La drammaturgia della partecipazione nel mondo digitale - Pizzo, Antonio (Mimesis Journal, 2017)
The essay discusses the new book of Andy Lavender (Performance in the Twenty-first Century: Theatres of Engagement, Routledge, London & New York 2016) and focuses on the new perspective it opens on the contemporary theatre after the postmodernism and the postdramatic. In particularly it compares the notion of theatre engagement with the contemporary digital culture and entertainment. A brief consideration about methodology of interdisciplinarity concludes the article.